Pancreatic and bile duct cancer circulating tumor cells (CTC) form immune-resistant multi-cell type clusters in the portal venous circulation. Issue 10 (3rd October 2018) - Arnoletti, J Pablo; Fanaian, Na'im; Reza, Joseph; Sause, Ryan; Almodovar, Alvin JO; Srivastava, Milan; Patel, Swati; Veldhuis, Paula P; Griffith, Elizabeth; Shao, Yai-Ping; Zhu, Xiang; Litherland, Sally A
ABSTRACT: Circulating tumor cells (CTC) enter the blood from many carcinomas and represent a likely source of metastatic dissemination. In contrast to the peripheral circulation, KRAS mutation- positive CTC thrive in the portal venous blood of patients with pancreatic ductal adenocarcinoma (PDAC). To analyze the essential interactions that contribute to carcinoma CTC growth and immune resistance, portal venous blood was collected during pancreatico-duodenectomy in 41 patients with peri-ampullary pathologies (PDAC = 11; ampullary adenocarcinoma (AA) = 15; distal cholangiocarcinoma (CC) = 6; IPMN = 7; non-malignant pancreatitis = 2). FACS-isolated cell populations from the portal circulation were reconstituted ex vivo using mixed cell reaction cultures (MCR). During the first 48hr, PDAC, AA, and CC patient CTC were all highly proliferative (mean 1.7 hr/cell cycle, 61.5% ± 20% growing cells) and resistant to apoptosis (mean 39% ±  25% apoptotic cells). PDAC CTC proliferation and resistance to T cell cytotoxicity were decreased among patients who received pre-operative chemotherapy (p = 0.0019, p = 0.0191, respectively). After 7 days in culture, CTC from PDAC, CC, and AA patients recruited multiple immune cell types, including CD105 + CD14 + myeloid fibroblasts, to organize into spheroid-like clusters. It was only in PDAC and CC-derived MCR that cluster formation promoted CTC survival, growth, and fibroblast differentiation. FACS depletion of CTC or myeloid fibroblast cells eliminated cluster network formation, and re-introduction of these cell populations reconstituted such ability. Our findings suggest that PDAC and CC CTC survival within the portal venous circulation is supported by their interactions with immune cells within multi-cell type clusters that could represent vectors of local recurrence and metastatic progression.